Sacred Sounds and Contested Spaces: Navigating Musical Ambivalence in NASFAT’s Islamic Worship Practices in Nigeria - Adejube, Samuel Ayoola; Ajala, Adebola Zainab (Àgídìgbo: ABUAD Journal of the Humanities, 2024)
Music occupies a contested space within Islamic worship, reflecting tensions between tradition, cultural adaptation, and contemporary spiritual practices. While many religious traditions, including Christianity and African Traditional Religions in Nigeria, seamlessly integrate music into worship, Islamic perspectives on music remain complex and ambivalent. This study explores the reception of music within the Nasrul-Lahi-il Fatih Society of Nigeria (NASFAT), a prominent Muslim prayer organisation known for its innovative approaches to Islamic practice. Employing ethnographic methods, including interviews and observation at the Samonda branch in Oyo State, Nigeria, the research investigates how NASFAT members navigate the intricate relationship between music and sacred spaces. Findings reveal that NASFAT adherents exhibit a nuanced understanding of music, recognising its pedagogical and spiritual potential for enhancing religious education and fostering devotion. However, significant ambivalence persists, with respondents distinguishing between the permissibility of music in secular versus liturgical contexts. While music is embraced during informal gatherings for its ability to convey sacred teachings and build community, its inclusion in formal worship settings remains contentious, with clerics citing concerns about preserving the sanctity of sacred spaces. This research concludes that music, as a dynamic form of spiritual expression, plays an essential role in fostering religious engagement and communal identity. It calls for a re-evaluation of traditional perspectives that restrict its liturgical use, advocating for a more inclusive understanding of music’s potential within Islamic worship practices. The findings contribute to broader discussions on religious identity formation, cultural innovation, and the evolving role of music in Islamic worship.